'Like a tongue to a loosening tooth': modernism and lyric. Issue 1 (2nd January 2018) - Hercock, Ned
ABSTRACT: What is the opposite of lyric? And how do we know? It seems right to think of many definitional modernist texts as 'anti-lyrical, pure and simple' (Adorno); of the lyric as 'precisely the antithesis of modernity' (de Man). But the anti-lyric moments I consider in this essay – largely the use of iteration, flatness and disgust in Beckett's Watt – show how lyric performance and its problems inhabit even the most stringently anti-lyric literary situations. While anti-lyrics such as Watt attest to the 'deep ludicrousness' of lyric, they also radicalise it by relentlessly subjecting it to its own formal logic: they are the process and products of such a radicalisation. In testing the conditions of aesthetic production and reception (nearly to destruction), they reveal some of the constitutive conditions and problematics of lyric writing and how it asks to be read. They further highlight the value and power of lyric in a way that sympathetic and non-dialectical readings – Hegelian but harmonising rather than disruptive – mostly fail to.